Metabolomics, antioxidant, and enzyme inhibitory effects of Citrus aurantium fruits - Eldahshan, Omayma A.; Bouabdallah, Salwa; Abd El-khalek, Rawan M.; El Hassab, Mahmoud A.; Zengin, Gokhan; Negmeldin, Ahmed T.; Khaleel, Eman F.; Eldehna, Wagdy M.; Mostafa, Nada M. (Frontiers in Chemistry, 2025)
IntroductionThe genus Citrus comprises a large number of economically important fruit crops. They are recognized globally as functional foods and in the food, pharmaceutical, and cosmetic industries.MethodsWe present herein the chemical composition of the hexane extracts of Citrus aurantium (bitter orange) fruits and leaves by GC-MS for the first time, in addition to their antioxidant and enzyme inhibitory activities in vitro.Results and DiscussionGC-MS revealed nootkatone (15.29%), decyl anthranilate (11.58%), neryl acetate (7.83%), and linalool acetate (6.83%) as major components of fruit extract; while the leaves extract contained mainly lupeol (24.32%), linalool (16.47%), friedelan-3-one (16.40%) and linalool acetate (12.31%). The extracts showed potential inhibitory activities against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), tyrosinase, amylase, and glucosidase enzymes. Results were confirmed by in silico molecular docking studies on the respective enzymes' active sites, viz NADPH oxidase, BChE, tyrosinase, α-amylase, and α-glucosidase. Amongst the docked compounds, lupeol showed the best binding affinities to NADPH oxidase, butyrylcholinesterase BChE, and α- glucosidase; while linalool acetate and neryl acetate showed the best activities against tyrosinase and α-amylase enzymes, respectively. In conclusion, bitter orange waste products can be a potentially important source of antioxidants and useful supplements.